KNOWLEDGE OF NURSING PROFESSIONALS REGARDING HAND HYGIENE - Flávia Maria Derhun; Verusca Soares de Souza; Maria Antônia Ramos Costa; Kelly Cristina Inoue; Laura Misue Matsuda (Universidade Federal do Paraná, 2016)
This quantitative analytical study, performed in January 2014, aimed to analyze the knowledge of nursing professionals regarding hand hygiene. Participants were 267 employees of two hospitals in the northwest of Paraná, who filled out an adapted questionnaire of the Ministry of Health, entitled Knowledge Test Regarding Hand Hygiene for Health Professionals, which contains eight questions. The data were processed using the Statistical Package for the Social Sciences 20 (SPSS) and Epi InfoTM 7.1.3. A high percentage of correct responses to the questions was found, except for those that referred to the Route of infection and Minimum rubbing time of hands with an alcohol preparation. It was concluded that 86.52% of the investigated professionals did not fully know the instructions for hand hygiene. It is suggested that the hand hygiene issue be addressed with the teams investigated through permanent educational processes, guided by active methods.